[RETRACTED:] Membaca Maqasid Al-Syari'ah dalam Konteks Kemaritiman dan Ketahanan Nasional - Jahar, Asep Saepudin; Lubis, Amany; Fahri, Muhamad (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
[This article is retracted because the authors have already submitted and published it elsewhere. The authors submitted it to another journal while the article was in the editorial process of Al-Manahij: Jurnal Kajian Hukum Islam.] [Editor-in-chief: Bani Syarif Maula] ****************************** This essay deals with the integration between Islamic law and maritime affairs and national defence. The ends of sharia play a significant role in providing a mechanism and its practical strategies on how maritime affairs and national defence to be developed. This study searches to highlight dimension integration between Islamic law, social and natural sciences. It elaborates on the making of Islamic values as the basis of maritime affairs, national defence in maintaining social and natural lives. The object of this study is maritime and national security which is used as data and research analysis on the integration of Islam, science and society. This research explains that the scope of Islamic values in terms of maritime and national security is part of the foundation for preserving life, property and the quality of the nation's next generation (preserving offspring). By employing Jasser Auda’s thoughts on specific maqāṣid, this paper argues that strengthening maritime affairs and national defence needs to be integrated with the ends of Islamic law.